Indução de resistência do meloeiro à Fusarium sp. com elicitores à base de silício - Porcino, Mirelly Miguel (2022)
The melon is one of the most cultivated and appreciated vegetables in the world, adapted to semi-arid climatic conditions. One of the obstacles to its production is the high susceptibility to pathogens. One of the main diseases that affect the melon is Fusarium wilt (Fusarium sp.), causing yield loss, damping off, plant death, fruit rot and unfeasibility of commercialization. The use of silicon-based resistance elicitors, associated with other management practices, can mitigate problems related to the attack of pathogens, in addition to providing improvements in the physiological and productive quality of the crop. In view of the above, the general objective of this research was to determine the influence of silicon-based products on melon plants and fruits (Cucumis melo L.) and its effect on Fusarium sp. The research was carried out at the Phytopathology Laboratory (LAFIT) of the Federal University of Paraíba, Campus II, Areia-PB. The elicitors used were Potassium Silicate (4L/100L), Organic Silicon (100g/100L), Agrosilicon® (3g/L), Rocksil® (3g/L), Salicylic Acid (2 mmol), Chelal® Si (2L/ 100L), in addition to the fungicide Thiabendazole® (400mL/100L) and the control (without treatment). Article I: The objective was to determine the effects of foliar application of silicon-based elicitors on productive and physiological aspects and on postharvest quality of yellow melon. Gas exchange in plants in the field, post-harvest (fruit weight, skin and pulp thickness, pulp firmness, total titratable acidity, hydrogenic potential, soluble solids content, SS/AT and vitamin C) and on the activity of enzymes peroxidases (PODs), polyphenoloxidases (PPOs), phenylalanine ammonia lyase (FAL). The elicitors did not influence the physical and chemical characteristics and enzymatic activity of melon fruits and did not change the biometric characteristics, productivity and chemical quality of fruits, in the two cultivation cycles. The elicitors promoted an increase in photosynthetic rate and transpiration of plants, however, they did not change the activity of PODs, PPOs and FAL enzymes. Article II: Aimed to verify the effect of silicon sources on Fusarium sp. in vitro and in yellow melon seedlings. The interaction between two Fusarium sp. and the in vitro elicitors, analyzing the mycelial growth rate index, percentage of growth inhibition, sporose production, percentage of sporulation inhibition. The most efficient treatments in inhibiting the growth and infection of the pathogen in both tests were Rocksil® and Thiabendazole®. Rocksil® and Potassium Silicate reduced the disease rate in melon seedlings. For biometric parameters and physiological responses, no differences were observed between treatments. Rocksil® is efficient in the in vitro control of Fusarium sp. Article III: The objective was to determine the efficiency of silicon-based elicitors in post-harvest quality and in the control of rot caused by Fusariumsp. in yellow melon fruits. The weight of fruits was analyzed; Peel and pulp thickness; pulp firmness; Total titratable acidity; Hydrogen potential; Soluble solids content; Ratio of Soluble Solids and Titratable Acidity; Vitamin C. In the fruit pathogenicity test, two Fusarium sp. measuring the diameter of the lesion. The activity of PODs, PPOs and FAL enzymes was evaluated. The elicitors did not reduce the severity of the disease caused by Fusarium sp. Agrosilicon® is efficient in activating phenylalanine ammonia-lyase in yellow melon fruits.